2021
DOI: 10.33084/jsm.v7i1.2656
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Program Pencegahan DBD terhadap Perilaku Masyarakat dalam Pengawasan dan Pemberantasan Jentik Nyamuk Demam Berdarah Dengue dengan Menerapkan Teori Health Belief Model

Abstract: Dengue Fever is a disease caused by the dengue virus with acute fever symptoms by entering the human bloodstream through the bite of a mosquito from the genus Aedes. Dengue Hemorrhagic Fever (DHF) has spread widely to all provinces in Indonesia. This disease often appears as an Extraordinary Event (KLB) with relatively high morbidity and mortality. Many dengue incidence rates make the application of the DHF prevention program by applying the theory of the Health Belief Model (HBM) as a prevention effort that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…This research is in line with Wahyudi and Ningrum's research (2021) which showed that there was an increase in the average value of five HBM indicators, namely perceived susceptibility, perceived severity, perceived benefit, perceived barrier, cues to action in eradicating larvae in the residents of Ngrancah Hamlet, Senggreng Village after being carried out intervention. 11 Research by Hanklang et al (2018) in Thailand also found that DHF prevention intervention programs significantly increased knowledge, per-ceived vulnerability, perceived severity, perceived benefits, perceived barriers and preventive actions.…”
Section: Entomologymentioning
confidence: 98%
“…This research is in line with Wahyudi and Ningrum's research (2021) which showed that there was an increase in the average value of five HBM indicators, namely perceived susceptibility, perceived severity, perceived benefit, perceived barrier, cues to action in eradicating larvae in the residents of Ngrancah Hamlet, Senggreng Village after being carried out intervention. 11 Research by Hanklang et al (2018) in Thailand also found that DHF prevention intervention programs significantly increased knowledge, per-ceived vulnerability, perceived severity, perceived benefits, perceived barriers and preventive actions.…”
Section: Entomologymentioning
confidence: 98%